(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The purpose of this study is to test a theoreticalcausal model concerning how elementary and secondary school principals caninfluence school student achievement through the frequency of implementation ofcertain instructional leadership behaviors. After controlling for contextualvariables, we hypothesized that three latent variables related to principalinstructional leadership (school governance, instructional organization, schoolclimate) affected student achievement. A total of 332 teachers and 56 schoolprincipals participated in the study. We conducted separate analyses of theproposed model at the individual and school level. The results confirm that theproposed model fit the data. We discuss the theoretical and practicalimplications of the results.